Sign Tracking, but Not Goal Tracking, is Resistant to Outcome Devaluation - Morrison, Sara E.; Bamkole, Michael A.; Nicola, Saleem M. (Frontiers in Neuroscience, 2015)
During Pavlovian conditioning, a conditioned stimulus (CS) may act as a predictor of a reward to be delivered in another location. Individuals vary widely in their propensity to engage with the CS (sign tracking) or with the site of eventual reward (goal tracking). It is often assumed that sign tracking involves the association of the CS with the motivational value of the reward, resulting in the CS acquiring incentive value independent of the outcome. However, experimental evidence for this assumption is lacking. In order to test the hypothesis that sign tracking behavior does not rely on a neural representation of the outcome, we employed a reward devaluation procedure. We trained rats on a classic Pavlovian paradigm in which a lever CS was paired with a sucrose reward, then devalued the reward by pairing sucrose with illness in the absence of the CS. We found that sign tracking behavior was enhanced, rather than diminished, following reward devaluation; thus, sign tracking is clearly independent of a representation of the outcome. In contrast, goal tracking behavior was decreased by reward devaluation. Furthermore, when we divided rats into those with high propensity to engage with the lever (sign trackers) and low propensity to engage with the lever (goal trackers), we found that nearly all of the effects of devaluation could be attributed to the goal trackers. These results show that sign tracking and goal tracking behavior may be the output of different associative structures in the brain, providing insight into the mechanisms by which reward-associated stimuli—such as drug cues—come to exert control over behavior in some individuals.